The glycinergic system in human startle disease: a genetic screening approach - Davies, Jeff S.; Chung, Seo-Kyung; Thomas, Rhys H.; Robinson, Angela; Hammond, Carrie L.; Mullins, Jonathan G.; Carta, Eloisa; Pearce, Brian R.; Harvey, Kirsten; Harvey, Robert J.; Rees, Mark I. (Frontiers in Molecular Neuroscience, 2010)
Human startle disease, also known as hyperekplexia (OMIM 149400), is a paroxysmal neurological disorder caused by defects in glycinergic neurotransmission. Hyperekplexia is characterised by an exaggerated startle reflex in response to tactile or acoustic stimuli which first presents as neonatal hypertonia, followed in some with episodes of life-threatening infantile apnoea. Genetic screening studies have demonstrated that hyperekplexia is genetically heterogeneous with several missense and nonsense mutations in the postsynaptic glycine receptor (GlyR) a1 subunit gene (GLRA1) as the primary cause. More recently, missense, nonsense and frameshift mutations have also been identified in the glycine transporter GlyT2 gene, SLC6A5, demonstrating a presynaptic component to this disease. Further mutations, albeit rare, have been identified in the genes encoding the GlyR b subunit (GLRB), collybistin (ARHGEF9) and gephyrin (GPHN) – all of which are postsynaptic proteins involved in orchestrating glycinergic neurotransmission. In this review, we describe the clinical ascertainment aspects, phenotypic considerations and the downstream molecular genetic tools utilised to analyse both presynaptic and postsynaptic components of this heterogeneous human neurological disorder. Moreover, we will describe how the ancient startle response is the preserve of glycinergic neurotransmission and how animal models and human hyperekplexia patients have provided synergistic evidence that implicates this inhibitory system in the control of startle reflexes.